2007
DOI: 10.1109/jsen.2007.897363
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive Humidity Sensors With High Sensitivity and Subsecond Response Times

Abstract: Capacitive-based humidity sensors were fabricated using coplanar interdigitated electrodes coated with nanostructured TiO 2 thin films produced by glancing angle deposition. In this letter, we show that increased sensitivity (nF/%RH) is obtained by decreasing the electrode periodicity or by increasing the planar area of the electrodes, or both. The devices were sensitive over a wide range of relative humidity levels ( 1% to 92%) and exhibited extremely fast, subsecond response times. Typical adsorption and des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 7 publications
(8 reference statements)
1
28
1
Order By: Relevance
“…Capacitance humidity sensors consisting of OAD TiO 2 nanostructures deposited on interdigitated electrodes were developed some time ago by Brett et al [202,[464][465][466]. Although other OAD materials respond to humidity variations (e.g., SiO 2 and Al 2 O 3 ), sensors utilizing TiO 2 exhibit the greatest change and show an exponential increase from $1 nF to $1 lF when the humidity changes from 2% to 92% [467].…”
Section: Gas and Vapor Sensorsmentioning
confidence: 99%
“…Capacitance humidity sensors consisting of OAD TiO 2 nanostructures deposited on interdigitated electrodes were developed some time ago by Brett et al [202,[464][465][466]. Although other OAD materials respond to humidity variations (e.g., SiO 2 and Al 2 O 3 ), sensors utilizing TiO 2 exhibit the greatest change and show an exponential increase from $1 nF to $1 lF when the humidity changes from 2% to 92% [467].…”
Section: Gas and Vapor Sensorsmentioning
confidence: 99%
“…17,18,25,[31][32][33] For example, it was reported that a highly organized Al 2 O 3 -based nanomaterial, deposited by glancing angle deposition (GLAD, which is a modified PVD deposition technique offering the possibility to control morphology on a 10 nm scale), is able to detect humidity change on a millisecond time scale, which is one of the fastest humidity sensor responses reported to date. 33 Single SnO 2 nanowires were obtained by a CVD technique and revealed high sensitivity to relative humidity. 25 The main disadvantages of sensors utilizing such materials for high volume applications are the need for extensive additional development to achieve reproducible process techniques suitable for implementation in a manufacturing environment and the increased cost of the sensors that would result from the use of expensive equipment in production (CVD, PVD, etc).…”
Section: ' Introductionmentioning
confidence: 99%
“…It has been previously shown that nanostructured thin films produced by glancing angle deposition (GLAD) [5]- [8] exhibit a measurable and repeatable response to variations in RH, while using optical and capacitive methods to observe these changes. Shifts in capacitance of three orders of magnitude have been observed for a change of RH from 2% to 92% [9]. In addition, extremely fast response times are observed, typically 90-300 ms [9]- [11].…”
Section: Introductionmentioning
confidence: 98%
“…Shifts in capacitance of three orders of magnitude have been observed for a change of RH from 2% to 92% [9]. In addition, extremely fast response times are observed, typically 90-300 ms [9]- [11].…”
Section: Introductionmentioning
confidence: 98%